ChemInform Abstract: 1, 3‐Dienones and 2H‐Pyran‐2‐ones from Soft α‐Vinyl Enolization of β‐Chlorovinyl Ketones: Defined Roles of Broensted and Lewis Base. Issue 19 (April 2016) - Kim, Hun Young; Oh, Kyungsoo
Abstract: The use of the Broensted base, Et3 N, along with a catalytic amount of Lewis base, PPh3, leads to the isomerization of chlorovinyl ketones affording 1, 3‐dienones.